POTENSI PENGEMBANGAN BADAN USAHA MILIK KAMPUNG SOTA, DISTRIK SOTA, KABUPATEN MERAUKE - hendricus Lembang (Musamus Journal of Economics Development, 2018)
Base on the Village Law No. 6 of 2014 concerning Village, namely villages have the right, authority and obligation to regulate and manage their own government affairs and community interests based on their rights of origin and local customs. In this authority, the village provides services to the community and conducts community empowerment. Sota village is a border region with Papua New Guinea. The location of Kampung Sota is relatively close to the seafront of the city of Merauke, has a population of 1,270 in 2014 and the resources of forests, rivers and swamps. This research use Participatory Rural Appraisal (PRA) approach and SWOT analysis. The results of the study found: Strength Aspects namely 1). Raw materials are easily available, 2). Strategic business location, 3). Product prices begin to increase, 4). The products produced are export products, 5). Availability of Village Land, 6). Commitment from the village government. Weakness aspects are: 1). The lack of business capital, small production quantity, 2). Transportation for raw materials, 3). Unattractive packaging, 4). Cooperatives in the village are controlled by individuals / traditional leaders who control the local land. Opportunity Aspect namely 1). Products that have a prospective market share, 2). Production capacity can be reproduced, 3). Increased consumer needs and public awareness to use local products, 4). Development of technology and information, 5). Additional workforce. Threat aspects, namely: 1). Still depends on the rainy and dry seasons, 2). Increased bargaining position of raw material suppliers, 3). The emergence of new competitors, 4). Government regulations on National Parks. So that the type of potential business that can be developed is the management of eucalyptus oil. While the alternative business sector is tourism, clean water, nine basic commodities and arwana fish. Keywords: Development, Village Owned Enterprises, prospective